Unilateral Laminotomy with Bilateral Spinal Canal Decompression for Lumbar Stenosis: A Technical Note - Moisi, Marc (Cureus, 2016)
Lumbar stenosis has become one of the most common spinal pathologies and one that results in neurogenic claudication, back and leg pain, and disability. The standard procedure is still an open laminectomy, which involves wide muscle retraction and extensive removal of the posterior spinal structures. This can lead to instability and the need for additional spinal fusion. We present a systemized and detailed approach to unilateral laminotomy for bilateral decompression, which we believe is superior to the standard open laminectomy in terms of intraoperative visualization, postoperative stability, and degree of invasiveness.